Transgeneridade: uma análise da transição de gênero no desempenho e nos papéis ocupacionais - ALMEIDA, Laiane de Sousa (2023)
This reaserch addresses possible relations between the gender transition and the occupational dimension, using the Model of Human Occupation as a theoretical contribution. In this way, the study have the objective analyze the relationship between gender transition, occupational performance and occupational roles of transgender people from the understanding of the occupational profile, the description of occupational performance before and after the gender transition in the areas of occupations Education, Work, Leisure and Health Management, followed by the identification and configuration of occupational roles in this process. This is a qualitative, descriptive and retrospective study, with a sample of 10 individuals, self- reported transgender, over 18 years old, accessed through the active search of the researchers. The instruments used for data collection were an interview to assess occupational profile and sociodemographic characterization, followed by another semi -directed interview about the process of gender transition and occupational performance, and finally the application of the Occupational Role Identification List protocol. The results indicated that after the gender transition there were positive and negative changes in occupational performance in all areas of occupation surveyed, promoting a reconfiguration in daily living standards. There was a reconfiguration in occupational roles, where the main gains after the transition were the insertion of the role of Worker, Volunteer and Participant in Organizations and the main role lost after the transition was the Religious. Given the results, is highlight the contribution of the study to the scientific field and the transgender population by bringing greater visibility to their experiences from their perceptions, including the occupational perspective. In addition, it is shown as an innovative research and of great relevance to the Occupational Therapy area, which from the data can broaden its spectrum of action and recognize the demands of this public. For this reason, further research in this field is suggested, further diversifying the sample, assessing other occupational aspects and exploring the various gender identities.